2008
DOI: 10.1038/icb.2008.57
|View full text |Cite
|
Sign up to set email alerts
|

A novel nervous system‐induced factor inducing immune responses in the spleen

Abstract: This study relates to a novel mediator signaling between the nervous system and the spleen following an immune challenge. Using enzyme-linked immunospot and cell proliferation assays, we found that supernatants of cultured splenocytes prepared from subcutaneously trypanosome-inoculated rats and mice spleens obtained immediately after inoculation and added to naive cells significantly stimulate interferon-c production and cell proliferation compared to phosphate-buffered saline-inoculated animals. This action w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 39 publications
1
18
1
Order By: Relevance
“…In the immune system, the spleen is the largest peripheral immune organ of the pig and plays a crucial role in maintaining immune homeostasis [9]. Studies have shown that Zn is associated with antioxidative and immune functions in the liver and serum, but it is less well known whether Zn has an immunoenhancement effect on the spleen [8].…”
Section: Introductionmentioning
confidence: 99%
“…In the immune system, the spleen is the largest peripheral immune organ of the pig and plays a crucial role in maintaining immune homeostasis [9]. Studies have shown that Zn is associated with antioxidative and immune functions in the liver and serum, but it is less well known whether Zn has an immunoenhancement effect on the spleen [8].…”
Section: Introductionmentioning
confidence: 99%
“…Recombinant wild type ISRAA used in this study was obtained as described previously (10). Mutated ISRAA was synthesized by site directed mutagenesis in which the predicted active site was deleted from the ISRAA gene and cloned in a pUC57 vector.…”
Section: Methodsmentioning
confidence: 99%
“…In the context of these neuroimmune interactions, in a recent study we described a novel nervous system-induced immune system-released activating agent (ISRAA)(10). It was revealed that this mediator is a signaling factor between the nervous system and the spleen following an immune challenge in mice.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…EU552928) (1) and is believed to mediate signaling between the nervous and the immune system. ISRAA was initially considered to have a cytokine-like activity due to several factors, including its relatively low molecular mass, its biological effects on a broad spectrum of cell types, such as T and B cells and monocytes/macrophages, the ability of the same cell populations to respond to ISRAA by producing cytokines, such as interferon (IFN)-γ, as well as the fact that ISRAA is lined up on chromosome 14 on the mouse system where several low molecular mass cytokines are mapped (1). Although ISRAA was identified in the mouse, the alignment has shown that the molecule has conserved regions between many species (2).…”
Section: Introductionmentioning
confidence: 99%